Business model innovation: towards a conceptual framework - Irina Saur-Amaral; Raquel Reis Soares; João F. Proença (Tourism & Management Studies)
Business model innovation (BMI) is core for entrepreneurship in industrial or service sectors, including tourism. Our submission focuses on the development of the field of BMI. We perform systematic literature review based on 316 valid papers indexed on ISI Current Contents, published between 2000 and 2015. Bibliometric results indicate a significant increase in the number of papers, journals and authors, and lack of specialized journals/authors publishing regularly in the BMI field. Thematic analysis reveals that BMI has been extensively studied, however there is rarely any cumulative knowledge effect between authors. Most researches were conceptual or qualitative, however few constructs have been defined and tested to enable quantitative studies. We conclude that there had been little evolution in terms of theoretically developing the BMI field. We argue that there is a need to adopt already existing conceptual models, develop constructs and validate them with primary quantitative data and advanced statistical analysis, in different research contexts.